Minerals and dietary fibre source snack made from Moringa leaves enriched with ginger - Kustiani, Ai; Adyas, Atikah; Nurdin, Samsu Udayana; Indriani, Yaktiworo (International Journal of Public Health Science (IJPHS), 2024)
The findings from the 2021 Indonesian Nutritional Status Study reveal a substantial 24.4% prevalence of child stunting, emphasizing the need for diverse strategies to achieve the desired target. One such strategy involves ensuring the nutritional well-being of expectant mothers to prevent stunting. Moringa leaves are a rich source of essential nutrients. Incorporating Moringa leaf powder into catfish flour-based snacks can boost their protein and mineral content while overcoming any undesirable odors, though this application is currently limited to crackers. This study aimed to create snack products using Moringa leaves, such as tea, brownies, and pudding, with the addition of ginger to enhance dietary fiber and mineral content for pregnant women. The top formulations identified through sensory assessment are F1 tea, F1 brownies, and F2 pudding. These specific tea, brownies, and pudding variations boast dietary fiber content exceeding 3 grams and meet or exceed 15% of the recommended daily intake levels for iron and zinc for pregnant women, as stipulated by the nutrition label reference. As a result, they can be classified as wholesome snacks rich in dietary fiber, iron, and zinc.